Reduction technique for n × n complex matrix systems. - Nik Long, Nik Mohd Asri; Eshkuratov, Zainidin K.; Sapar, Siti Hasana (Hikari Ltd, 2009)
In this short paper, we describe a technique of reducing the system of complex matrix equations obtained from solving the system of hypersingular integral equation, into the real system of algebraic equations, in which it can be solved numerically. The example of using of the technique is shown.